The consumption of generic medicaments: perception and level of knowledge - Ribeiro, Maria Isabel (2015)
Introduction: The generic medicine has the same qualitative and quantitative composition in active substances, pharmaceutical form and dosage, administered by the same way with the same therapeutic indication and security than the reference medicine (1). Objectives: To analyze the perception and level of knowledge about generic medicines and to study the correlation with socio-economic variables such as education level, monthly medicines expenses, employment, age and gender. Materials and Methods: It was developed a cross-sectional study. A non-probabilistic sample of 381 individuals was collected in northern Portuguese localities during January and February 2015. To collect the data was applied a questionnaire developed by Lopes, Silva, Pinto e Ribeiro (2). Most respondents were female (53.5%) with ages between 18 and 88 years. Results and Discussion: The level of knowledge about generic medicines was very poor (14.8%); poor (21.0%); fair (39.9%); good (23.1%) and very good (1.2%). Most respondents (91.4%) consumed generic medicines although they consider that reference medicines are more effective. The level of knowledge is positive correlated with the education level and negatively correlated with age and monthly medicines expenses. Gender was associated with the level of knowledge. Employment wasn’t associated with the level of knowledge. Conclusion: A significative proportion of respondents were misinformed about generic medicines, preferring to consume the reference medicines that they consider more effective. According to the literature, doctors are primarily responsible by the scarce information provided to the patient about generic medicines and by not prescribing these medicines. References: 1. Branco, M. & Nunes, B. (2009). Uma observação sobre o consumo de Genéricos. Departamento de Epidemiologia. Instituto Nacional de Saúde, Doutor Ricardo Jorge. Lisboa. 2. Lopes, C.; Silva, F.; Pinto, Isabel; Ribeiro, Maria (2011). A perspectiva dos consumidores portugueses sobre os medicamentos de marca vs medicamentos genéricos. In XXV Encontro Nacional APLF. Coimbra.